ODL Centralized Control of Power Communication Network Based on Bio-Inspired Algorithms and SDN - Min, Congcong (Mathematical problems in engineering, 2022)
An ODL centralized control strategy is designed to study the problem of heavy load in the power communication network, in which the machine learning method is introduced. SDN technology is used to establish SDN cluster control structure, and different algorithms, such as genetic algorithm, are utilized to optimize resource scheduling. The results show that the improved algorithm obtains the shortest link path through 28 iterations. At the same time, AHP is used to switch the network spectrum. Moreover, the application effect of the control strategy is simulated and analyzed, and its effect on network communication application is verified.